Injury of leg somatotopy of corticospinal tract at corona radiata by ventriculoperitoneal shunt: A case report - Jang, Sung Ho (Medicine (Baltimore), 2018)
RATIONALE: A 45-year-old right-handed female patient suffered head trauma after being hit by a truck that ran into a house. PATIENT CONCERNS: The patient lost consciousness for 1 hour and experienced posttraumatic amnesia for 1 month after the accident. DIAGNOSES: She underwent conservative management for a subdural hematoma in the left frontotemporal lobes and intracerebral hematoma in the left frontal lobe. INTERVENTIONS: The patient's Glasgow Coma Scale score was 11. She underwent a VP shunt operation, approached through the right posterior parietal area of the brain, at 4 months after onset. Approximately, 6 months after onset, she was admitted to the rehabilitation department of a university hospital. She presented with moderate weakness of the left leg: Medical Research Council scores: hip flexor; 3, knee extensor; 3+, ankle dorsiflexor; 3–. Brain magnetic resonance imaging revealed a leukomalactic lesion in the right posterior corona radiata along the shunt. OUTCOMES: On 6-month (2 months after the shunt operation) diffusion tensor tractography, the left CST showed partial injury in the posterior portion compared with the right CST. On 6-month transcranial magnetic stimulation study, the motor-evoked potential obtained at the left tibialis anterior muscle revealed lower amplitude than that on the right side. LESSONS: Injury of leg somatotopy of a CST was demonstrated in a patient with leg weakness following a VP shunt operation.